“El enemigo en casa: el parricidio y otras formas de violencia interpersonal doméstica en el Madrid de los Austrias (1580-1700)” - Blanca Llanes Parra (Nuevo mundo - Mundos Nuevos, 2008)
This paper focuses on the subject of the violence in the bosom of the families in Early Modern Madrid. It will analyse the parricide crimes, paying special attention to marital violence considering its significant presence in the criminal records. In order to undertake this research, the Inventario General de Causas Criminales, from the archive of the Sala de Alcaldes de Casa y Corte, corresponding to the period 1580-1700, has been used as the main documentary source. Likewise, the statistical data provided by the mentioned catalogue has been confronted with other documental evidences, both juridical and literary (Madrid’s chronicles from the Seventeenth Century).